The University’s Innovative Activity and the Real Sector of the Economy - V. N. Popov; A. N. Kharin; D. A. Zhukalin (Высшее образование в России, 2018)
The paper examines the areas and mechanisms of cooperation between business interests and Voronezh State University. It presents the successful  practices of implementing joint projects in the field of creating high-tech  industries and providing advanced training for engineering and technical  workers. The general prospect of the cooperation is the development of the  common educational, scientific and technological space of the Central Black  Earth economic region. One of the effective tools for interaction between  companies and universities is joint department. Voronezh State University  has established joint departments “Molecular biotechnology”, “Power  electronics”, “Communication Electronic Warfare Systems”. The other  important area of university’s participation in the development of the  regional industry is implementation of the federal target program “Research  and development on priority directions of development of scientific- technological complex of Russia for 2014–2020 years”. In 2017 VSU was a  participant of nine technological platforms. Another instrument to provide  interaction between business and university is creation of small innovation enterprises. In 2017 there were 31 small enterprises at VSU. It is  worth mentioning special projects related to working out of skill development and vocational training programs. VSU offers such programs at corporate  learning centers (T-Systems, J&M Management Consulting, Atos IT Solutions  and Services, PricewaterhousCoopers (PwC), DSR Corporation, OTSL Inc.,  NetCracker, DataArt, Microsoft, P&G and others). The effective scientific and  educational environment based on the interaction between universities and  enterprises will promote the development of interdisciplinary initiatives, joint  researches, advanced educational programs, creation of joint research  centers.